Lutetium-177–PSMA-617 for Metastatic Castration-Resistant Prostate Cancer - Sartor, Oliver; de Bono, Johann; Chi, Kim N; Fizazi, Karim; Herrmann, Ken; Rahbar, Kambiz; Tagawa, Scott T; Nordquist, Luke T; Vaishampayan, Nitin; El-Haddad, Ghassan; Park, Chandler H; Beer, Tomasz M; et al. (The New England journal of medicine, 2021)
Guiding the beta-emitting isotope lutetium-177 to prostate cancer lesions with the prostate-specific membrane antigen–targeted radioligand 177 Lu-PSMA-617 plus using standard care was compared with standard care in patients with metastatic castration-resistant prostate cancer. The radioligand therapy prolonged progression-free and overall survival. Adverse effects were more common, but quality of life was maintained.